Tramadol enhances PGF2α-stimulated osteoprotegerin synthesis in osteoblasts. Issue 8 (August 2020) - Kim, Woo; Tanabe, Kumiko; Kuroyanagi, Gen; Matsushima-Nishiwaki, Rie; Fujita, Kazuhiko; Kawabata, Tetsu; Sakai, Go; Tachi, Junko; Hioki, Tomoyuki; Nakashima, Daiki; Yamaguchi, Shinobu; Otsuka, Takanobu; et al.
Abstract: Osteoprotegerin (OPG) synthesized by osteoblasts is currently considered a crucial regulator to suppress the formation and function of osteoclasts. We previously showed that the synthesis of OPG is stimulated by prostaglandin F2α (PGF2α ) in the involvement of p38 mitogen-activated protein kinase (MAPK), stress-activated protein kinase/c- Jun N-terminal kinase (SAPK/JNK) and p44/p42 MAPK in osteoblast-like MC3T3-E1 cells. We also found that Rho-kinase is involved in the signaling of PGF2α upstream of p38 MAPK in these cells. Tramadol is widely used to treat chronic pain, such as low back pain associated with osteoporosis. We investigated whether or not tramadol affects the OPG release induced by PGF2α in osteoblast-like MC3T3-E1 cells. The levels of OPG in the conditioned medium were measured by an enzyme-linked immunosorbent assay. The mRNA expression of OPG was determined with real-time reverse transcription polymerase chain reaction. The phosphorylation of target protein was determined with a Western blot analysis. PGF2α induced the release and the mRNA expression of OPG, which tramadol significantly enhanced. Morphine, a selective μ-opioid receptor (MOR) agonist, also enhanced the PGF2α -induced OPG release. In addition, naloxone, a MOR antagonist, suppressed the enhancement by tramadol or morphine of the PGF2α -induced OPG synthesis. Tramadol upregulated the phosphorylation of SAPK/JNK and p38 MAPK stimulated by PGF2α but not that of p44/p42 MAPK or myosin phosphatase targeting protein (MYPT), a substrate of Rho-kinase. The inhibitors of both p38 MAPK and SAPK/JNK, SB203580 and SP600125, respectively, reduced the tramadol amplification of OPG release stimulated by PGF2α . The present results strongly suggest that tramadol enhances the synthesis of OPG stimulated by PGF2α through MOR in osteoblasts, and that the amplifying effect is exerted at upstream of p38 MAPK and SAPK/JNK but downstream of Rho-kinase. Abstract : Tramadol; μ-opioid receptor; PGF2α ; osteoprotegerin; MAP kinase; osteoblast.; Pharmaceutical chemistry; Cell biology; Pharmaceutical Science; Biochemistry; Bone; Pain Management; Pharmacology